2012
DOI: 10.1021/jp302225u
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Sensitive Photoconductivity of Porphyrin-Functionalized ZnO Nanorods

Abstract: Hybrid materials based on wide band gap semiconductors and dye molecules are intensively studied for photovoltaic applications. However, these materials also possess interesting gas sensitivities, besides these photonic effects. In this Article, we report the study, under visible light illumination, of the porphyrin-functionalized ZnO nanorod photoconductivity changes, modulated by exposure to two volatile organic compounds, ethanol and triethylamine, chosen as model analytes. The sensitivity to triethylamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…The variation of photoconductivity was modulated by exposure to two volatile organic compounds, ethanol and triethylamine, chosen as model analytes. 285 The sensitivity to triethylamine exceeded that to ethanol by more than two orders of magnitude, showing a selectivity that is not found in other porphyrin-based gas sensors. To investigate the mutual relationship between the photosensitivity and the gas sensitivity in porphyrin-functionalized ZnO nanorods, measurements of porphyrin-ZnO structures were performed in the dark, under visible light and exposed to organic vapors, using free-bases TPP, TPP-CO 2 H and their zinc complexes.…”
Section: Zinc Oxidementioning
confidence: 90%
See 2 more Smart Citations
“…The variation of photoconductivity was modulated by exposure to two volatile organic compounds, ethanol and triethylamine, chosen as model analytes. 285 The sensitivity to triethylamine exceeded that to ethanol by more than two orders of magnitude, showing a selectivity that is not found in other porphyrin-based gas sensors. To investigate the mutual relationship between the photosensitivity and the gas sensitivity in porphyrin-functionalized ZnO nanorods, measurements of porphyrin-ZnO structures were performed in the dark, under visible light and exposed to organic vapors, using free-bases TPP, TPP-CO 2 H and their zinc complexes.…”
Section: Zinc Oxidementioning
confidence: 90%
“…272 ZnO nanorods were grown via hydrothermal route from a seed layer deposited with a drop-coating method in the gap and on the rims of the ITO layer. 285 In order to achieve a homogeneous and controlled layer of ZnO, an array of seed layer spots was deposited by an automatic dispenser, controlling the diameter of droplets, of the spots, and the distance among spots 286 (Figure 77).…”
Section: Zinc Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…The effects of illumination and gas adsorption are adequately detected, measuring either the conductivity or the surface potential. In the case of conductivity, a network of nanorods was formed between ITO electrodes on glass [76]. Nanorods were drop casting coated with a layer of H 2 TPP terminated by a carboxyl group to promote binding onto the ZnO surface [77].…”
Section: Porphyrins Functionalized Conductive Materialsmentioning
confidence: 99%
“…We found that in porphyrins-coated nanorods, the exposure to visible light largely improved the sensitivity of the conductivity with respect to electron donating species such as amines [6]. Further studies have shown that a similar behavior is also shown by the surface potential measured by a Kelvin probe [7].…”
Section: Introductionmentioning
confidence: 99%